2015
DOI: 10.1007/s00127-015-1084-4
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of mental disorders and perpetration of domestic violence among military populations

Abstract: Purpose Military populations may experience more severe forms of domestic violence than the general population. Although mental disorders are associated with domestic violence perpetration among the general population, it is not clear whether this is the case for military populations. This review aimed to establish the prevalence and odds of domestic violence perpetration among male and female military personnel with mental disorders. Methods Systematic review: searches of eleven electronic databases were supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 51 publications
4
29
0
2
Order By: Relevance
“…Youth reporting PTSD symptoms were significantly more likely to report engaging in violent behaviours compared to youth not exposed to PTE. These findings suggest that PTSD may be an equally important factor to understand violent behaviours in adolescents as previously shown in adult veterans [13].…”
Section: Ptsd and Pte Without Ptsd As Correlates Of Self-reported Viosupporting
confidence: 70%
“…Youth reporting PTSD symptoms were significantly more likely to report engaging in violent behaviours compared to youth not exposed to PTE. These findings suggest that PTSD may be an equally important factor to understand violent behaviours in adolescents as previously shown in adult veterans [13].…”
Section: Ptsd and Pte Without Ptsd As Correlates Of Self-reported Viosupporting
confidence: 70%
“…Certain results have corroborated earlier findings involving Vietnam veterans and a consistent conclusion is that service members and veterans suffering from war-related PTSD have high prevalence rates of intimate partner violence (IPV) (e.g., Orcutt et al, 2003 ; Marshall et al, 2005 ; Taft et al, 2011 ; Smith et al, 2015 ; Trevillion et al, 2015 ). For example, in a recent systematic research review of military IPV prevalence, a 27.5% prevalence rate was found based on the studies reviewed of male veterans with PTSD who reported past year physical violence perpetration against female partners (Trevillion et al, 2015 ). This rate is substantially higher than the 12.7% IPV prevalence rate found in a nationally representative sample of participants with PTSD (Smith et al, 2015 ).…”
Section: Introductionsupporting
confidence: 74%
“…Living in a military environment as a unique job and lifestyle may highly affect physical and mental status of military personnel12; because of regular sports programmes, military men may have better physical fitness compared with general population 13. In the present study, military men had lower BMI, diabetes and hyperlipidaemia that could be reflectors of better physical fitness in this patient group—on the other hand, younger age and higher prevalence of hypertension in military men showed that factors other than physical fitness may play a role in CAD.…”
Section: Discussionmentioning
confidence: 99%